A geospatial approach in modeling urban land development and redevelopment of Bandar Abbas, Iran - Dadras, Mohsen (2015)
In general, the objective of this study is to arrive at a better understanding of spatio-temporal dynamics of urban growth through integration of mathematical and statistical models and data remote sensing (RS), and the techniques of GIS. Bandar Abbas is the study area of this research. Bandar Abbas has been facing many problems such as decayed urban district, unbalance and interaction of uses, restrictions of lands suitable for development, and physical limitation in urban sprawl due to the irregular growth, increasing migration of population and the lack of planning in urban management. The remote sensing data were used to calculate the urban sprawl and changes in land use. The results indicate that from 1956-2012, the urban area has increased from 403.77 hectares to 4959.59 hectares and the population of the city has grown to more than 30 times in the past six decades. The sprawl of the urban boundary of Bandar Abbas is determined by using the aerial photos and satellite images of 5 periods in over 56 years in this study. The comparison of the results obtained from the analysis of the master plan show that in terms of the pattern of land-use changes in the fundamental changes over the past 60 years has been created. However, such comparison indicates that the current situation is a continuation of the past and the irregularity of urban growth from a lack of appropriate allocation of land use and lack of knowledge about the land use changes over the past years. The first objective of the research and results obtained from the use of spatial data with high spatial resolution are upgraded and the master plan of land use is refined to identify the finer land use changes. Then, in order to identify the process of urban sprawl over time, the official boundary of Bandar Abbas was divided which is placed in a circular area in 32 geographical directions. The statistical models of Pearson chi-square and the Shannon's entropy were used to calculate the degree-of-freedom and degree-of-sprawl used in the analysis of urban growth. The results of the analysis show that Bandar Abbas enjoys high degree-of-freedom and degree-of-sprawl and negative value of degree-of-goodness. The second objective of the study was to analyze the pattern and process of urban growth over the past 60 years. To achieve the second objective of the study, the remote sensing data with high spatial resolution are used in order to extract the built-up areas. Further, the use of statistical models and its analysis to identify more precisely the pattern and process of urban growth in the past 60 years are also utilized. The analysis of remote sensing data in the 60-year period show that more than 50 percent of the urban area in Bandar Abbas city in decayed areas is scattered. The criteria and sub-criteria effective in urban development and redevelopment were determined based on experts' opinions, model of Pathway Analysis and creation of statistical database based on questionnaires. The analysis is performed by entering the intended variables and to use the mathematical and statistical formula and GIS tools. The qualitative and quantitative models such as Analytical Hierarchy Process (AHP), Fuzzy AHP, Frequency Ratio, Weighting index, and Weighting factor are used in this study for identification of lands suitable for development and redevelopment. TOPSIS model is used as an ideal solution to identify and prioritize appropriate lands identified. Then, the models of smart growth (TND, RCD and SD) and Smart Code are applied for the planning of lands identified. The correlation between the 1300 points sampled and field observations show that the Fuzzy AHP model has the most significant correlation (R2= 0.822) with the reality. Eastern and southern neighborhoods of the city have a great potential for urban development. Based on the models used in identifying suitable land for urban redevelopment, Frequency Ratio model has the most significant correlation (R2= 0.918) with the reality. The central, southern and southwestern areas adjacent to Bandar Abbas have great potential for urban redevelopment. For third and fourth objective of the study, a novel method is used for identification of suitable land for development and redevelopment in urban areas. Using the results obtained in this study, a novel method to identify the following effective criteria and sub-criteria, determine the suitable land for urban development and redevelopment, provide planning and land management solution based on smart growth model and taking into account the actual conditions existing in parallel developed and presented.